DISTRIBUSI USIA TENAGA KEPENDIDIKAN DARI EMPAT PROVINSI BEDASARKAN DATA KEMENDIKBUDRISTEK TAHUN 2023 - Ridho Firdaus; Hafid Dwi Januar; Haikal Muzakkii; Satrio Dwi Cahyo (CV. Multi Kreasi Media, 2024)
This study aims to understand the age distribution of educators in four provinces in Indonesia, to identify potential age gaps. The methods used are quantitative and descriptive statistical analysis, using data from the Ministry of Education and Culture portal in 2023. Analysis includes measures of centralization and deployment, as well as visualization of data. The results of the study show that private education personnel are dominated by the age group of 26-30 years, with a significant difference in the number of teachers in public schools compared to private schools. This study provides recommendations related to the management of educators, especially recruitment and regeneration, as well as avoiding the age gap between regions. These findings can be an input for policymakers in managing educator resources in Indonesia.